Properties of Co-deposited indium tin oxide and zinc oxide films using a bipolar pulse power supply and a dual magnetron sputter source - Hwang, MS; Jeong, HS; Kim, WM; Seo, YW (A V S AMER INST PHYSICS, 2003)
Multilayer coatings consisting of metal layers sandwiched between transparent conducting oxide layers are widely used for flat panel display electrodes and electromagnetic shield coatings for plasma displays, due to their high electrical conductivity and light transmittance. The electrical and optical properties of these multilayer films depend largely on the surface characteristics of the transparent conducting oxide thin films. A smoother surface on the transparent conducting oxide thin films makes it easier for the metal layer to form a continuous film, thus resulting in a higher conductivity and visible light transmittance. Indium tin oxide (ITO) and zinc oxide (ZnO) films were co-deposited using a dual magnetron sputter and a bipolar pulse power supply to decrease the surface roughness of the transparent conducting oxide films. The symmetric pulse mode of the power supply was used to simultaneously sputter an In2O3 (90 Wt %) : SnO2 (10 wt %) target and a ZnO target. We varied the duty of the pulses to control the ratio of ITO : ZnO in the thin films. The electrical and optical properties of the films were studied, and special attention was paid to the surface roughness and the crystallinity of the films. By co-depositing ITO and ZnO at a pulse duty ratio of ITO:ZnO=45:45 using a dual magnetron sputter and a bipolar pulse power supply, we were able to obtain amorphous transparent conducting oxide films with a very smooth surface which had a Zn-rich buffer layer under a In-rich surface layer. All of the films exhibited typical electrical and optical properties of transparent conducting oxide films deposited at room temperature. (C) 2003 American Vacuum Society.
Keywords: THIN-FILMS; TEMPERATURE; TRANSPARENT